Factors Related To Disability Inclusive Public Transport In A City In Peru - et. al., Karin Ponce Rojas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aims: In Latin America and the Caribbean, a large percentage of the urban and interurban transport service remains inaccessible for citizens with a disability. In Peru, citizens with complex disabilities have been made invisible in the public transport service. The objective of this research is to determine the relationship between the management of inclusive urban public transport and the accessibility of persons with disabilities in the city of Trujillo, 2020, and how public management impacts on this group of citizens. Methodology: A questionnaire was used based on the dimensions of each variable. The variables were: Inclusive urban public transport management composed of 5 dimensions (equipment and services, adapted vehicles, preferential rate, regulatory compliance, state of the roads) and accessibility of people with disabilities, composed of 5 dimensions (physical environment, attitudinal, social activities, mobility, comfort). Spearman's rank correlation was used. Results: The results allowed identifying that the management of inclusive urban public transport in the city of Trujillo has a predominantly deficient level, and the accessibility of people with disabilities is mainly poor. Conclusion: A direct and significant relationship was evidenced between the management of inclusive urban public transport and its dimensions (equipment and services, adapted vehicles, preferential rates, regulatory compliance, state of the roads) with the accessibility of people with disabilities in the city of Trujillo. Social activities, mobility and comfort, as well as preferential rate, normative compliance and state of the roads are decisive for the study of the relationship between the management of inclusive urban public transport and accessibility for the disabled.